Electric generator based on triboelectric effect - Ng, Raymond Shen Jie (Nanyang Technological University, 2022)
With rise in trend in nanotechnology there’s interest in finding method to convert mechanical to electrical energy with a miniaturized mechanism that can self-sustain as a standalone system rather than powered by a power supply. Although there are a few methods of converting mechanical energy to electrical energy such as electromagnetic induction, piezoelectric effect and electrostatic induction methods. Unfortunately, electric generators based on electromagnetic induction are very hard to be downsized to micro or submicron scales. As for electric generators based on piezoelectric and electrostatic induction, their internal resistance is typical very high up to several tens of megaohms. This project aims to study a typical of noval electric generators that convert mechanical to electrical energy with tribovoltaic effect. Tribovoltaic effect is the electric current generation when a semiconductor or metal electrode is slid against another semiconductor electrode. When the two electrodes are in contact, a p-n junction (or Schottky junction) is established around the contact interface. Frictional motion between them leads to creation of electrons and holes which then swept out of the junction, generating a DC current whose flowing direction is consistent with the built-in electric field in the junction. In this project, a structure of carbon cloth/semiconductor wire is used as the electric generator that is found to create a DC current under ultrasonic vibrations. The advantage of this mechanism is the ability to produce direct current directly instead of alternating current without the means of rectification and a lower internal resistance. In addition, the electric generators based on tribovoltaic effect can be constructed with metal and semiconductors, which could directly integrate with semiconductor devices and IC circuits.